Review: exploring the potential of Nigella sativa for tooth mineralization and periodontitis treatment and its additive effect with doxycycline - Akmal Ismail, Nurul Fitriatul (IIUM Press, 2022)
Oral disease has been a worldwide concern as the incidence and cost of treatment continues to rise. Management of the disease is challenging as success is often influenced by an individual’s lifestyle and diet. Nigella sativa (N. sativa) or black seed is a medicinal plant that has received growing interest due to its effectiveness against various conditions including cardiovascular disease, diabetes, cancer, as well as infectious diseases caused by bacterial, viral, and fungal infections. This narrative review studies N. sativa that has also shown great potential in dental health attributed to its role in stimulating the process of remineralization. Apart from that, N. sativa promotes healing of oral tissues as it induces the differentiation potential of heterogeneous cell populations in periodontal ligament cells. The anti -osteoporotic, antioxidant and anti-inflammatory properties of N. sativa also improve periodontal healing, particularly by preventing further destruction of bone components. This article discusses the occurrence of periodontitis and the therapeutic role of N. sativa with emphasis on the regulation of genes, for instance, the alkaline phosphatase (ALP) that is involved in tissue specialization and remineralization. It is speculated that the activity of N. sativa in remineralization can be enhanced by combination with other commonly used periodontitis antibiotics such as doxycycline. N. sativa is purported to induce periodontal tissue regeneration whilst minimizing toxicity. Thus, it may serve as an alternative or enhance the existing treatment for periodontitis when administered as a combined formulation.